2020
DOI: 10.21203/rs.3.rs-20641/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Best Choices: the Diversity and Functions of the Plants in the Home Gardens of the Tsang-la (Motuo Menba) Communities in Yarlung Tsangpo Grand Canyon, Southwest China

Abstract: Abstract Background: Home garden is identified as a kind of small-scale land-use system which is used to manage and cultivate useful plants by local people, and home gardens can provide various plant products and services. Investigating home gardens was regarded as an effective way to understand the biodiversity related local knowledge and culture of native people in Ethnobiology and Ethnoecology. Home garden is important in less developed and remote areas. The grand ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…This finding indicates the presence of high level of agreement on cultural relevance of species, and the sharing of common knowledge on useful species by homegarden owners. This finding is supported with that of [ 23 , 38 ]. In this study, the multipurpose species that have been identified in a wide number of home gardens (greater FC) were given first place for conservation and cultural use.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding indicates the presence of high level of agreement on cultural relevance of species, and the sharing of common knowledge on useful species by homegarden owners. This finding is supported with that of [ 23 , 38 ]. In this study, the multipurpose species that have been identified in a wide number of home gardens (greater FC) were given first place for conservation and cultural use.…”
Section: Discussionsupporting
confidence: 87%
“…They also meet social necessities and give environmental administration besides serving additionally as a source of income [ 22 ]. Thus, researching home gardens was viewed as an efficient technique to learn the biodiversity-related local knowledge and culture of native people [ 23 ].…”
Section: Introductionmentioning
confidence: 99%